2007
DOI: 10.1007/s12028-007-0034-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Brain

Abstract: Drug delivery to the brain has remained one of the most vexing problems in translational neuroscience research. This review rationalizes the strategies to target drugs to the brain. Factors such as the speed of intervention, the scale of intervention, the state of BBB, and the permissible risks, will all be critical in deciding how best to deliver drugs to a target site in the brain for a specific clinical situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 85 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…IA drug delivery is optimal when there is low cerebral blood flow (CBF), high regional uptake, and high systemic clearance [5-7]. In previous studies, we have shown the effectiveness of TCH in improving the IA delivery or pharmacological effects of unencapsulated drugs [8-10].…”
Section: Introductionmentioning
confidence: 99%
“…IA drug delivery is optimal when there is low cerebral blood flow (CBF), high regional uptake, and high systemic clearance [5-7]. In previous studies, we have shown the effectiveness of TCH in improving the IA delivery or pharmacological effects of unencapsulated drugs [8-10].…”
Section: Introductionmentioning
confidence: 99%
“…2,10 Consequently, intracarotid delivery can serve as the primary method of drug delivery or the technique could be used to increase the effectiveness of other methods of brain-selective drug delivery that target specific characteristics of the blood brain barrier (BBB). 11 Currently, intracarotid drugs are used for localizing neurological functions in the brain, and for the treatment of intractable cerebral vasospasm, ischemic strokes, and intracranial malignancies. 12 …”
Section: Introductionmentioning
confidence: 99%